1979
DOI: 10.1111/j.1471-4159.1979.tb11096.x
|View full text |Cite
|
Sign up to set email alerts
|

STIMULATORY EFFECT OF l‐GLUTAMATE AND RELATED AMINO ACIDS ON [3H]DOPAMINE RELEASE FROM RAT STRIATUM: AN IN VITRO MODEL FOR GLUTAMATE ACTIONS

Abstract: Abstract— The effects of l‐glutamate and a number of structural analogues on the spontaneous release of [3H]dopamine from slices of rat striatum were examined. Glutamate, and other excitatory amino acids produced a marked stimulation of [3H]DA release which was Ca2+‐dependent and unaffected by either procaine or tetrodotoxin. The glutamate‐stimulated release was abolished in kainate‐lesioned striatum. The action of glutamate was effectively antagonised by glutamamate diethylester and 2‐amino‐4‐phosphonobutyric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
1
2

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(99 citation statements)
references
References 42 publications
8
88
1
2
Order By: Relevance
“…Dopaminergic and glutamatergic terminals are localized in close opposition to each other on the same postsynaptic pyramidal cell (Smiley et al, 1994). NMDA receptors are known to interact with the central dopaminergic system (Roberts and Anderson, 1979;Carter et al, 1988;Johnson and Jones, 1990;Krebs et al, 1991;Morari et al, 1993;Youngren et al, 1993;Tsukada et al, 2000bTsukada et al, , 2001b. Furthermore, NMDA receptor antagonists reduce GABA release.…”
Section: Discussion the Role Of Da/glutamic Acid And Working Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Dopaminergic and glutamatergic terminals are localized in close opposition to each other on the same postsynaptic pyramidal cell (Smiley et al, 1994). NMDA receptors are known to interact with the central dopaminergic system (Roberts and Anderson, 1979;Carter et al, 1988;Johnson and Jones, 1990;Krebs et al, 1991;Morari et al, 1993;Youngren et al, 1993;Tsukada et al, 2000bTsukada et al, , 2001b. Furthermore, NMDA receptor antagonists reduce GABA release.…”
Section: Discussion the Role Of Da/glutamic Acid And Working Memorymentioning
confidence: 99%
“…NMDA receptors are known to interact with the central dopaminergic system (Roberts and Anderson, 1979;Carter et al, 1988;Krebs et al, 1991;Morari et al, 1993;Youngren et al, 1993;Tsukada et al, 2000bTsukada et al, , 2001b. Dopamine (DA) innervation of PFC is considered to be highly responsive to NMDA receptor antagonists (Deutch et al, 1987;Bowers and Morton, 1994;Hondo et al, 1994;Carlezon and Wise, 1996;Verma and Moghaddam, 1996;Jentsch et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacologic studies have found that glutamate applied to striatal slices in vitro stimulate [3H]DA release even in the presence of tetrodotoxin (Roberts and Anderson 1979;Giorguieff et a1. 1977;Marien et al 1993).…”
Section: Electrical Stimulation Of the Medial Prefrontal Cortex Incrementioning
confidence: 99%
“…Glutamate infusion into the striatum elevates extracellular dopamine, but this effect is insensitive to the perfusion of the sodium channel blocker tetrodotoxin (TTX) (Giorguieff et al, 1977;Roberts and Sharif, 1978;Roberts and Anderson, 1979;Marien et al, 1983;Clow and Jhamandas, 1989;Lonart and Zigmond, 1991; but see Youngren et al, 1993). Disinhibition of prefrontal cortex by local interference with GABAergic transmission (Karremann and or by GABA infusion into the medial thalamus (Romo et al, 1986a,b) similarly increases striatal dopamine levels while, at least in the latter case, inhibiting the firing of the ventral tegmental dopaminergic neurons that project to the striatum.…”
mentioning
confidence: 99%